2009
DOI: 10.1007/s10637-009-9313-x
|View full text |Cite
|
Sign up to set email alerts
|

DH9, a novel PPARγ agonist suppresses the proliferation of ADPKD epithelial cells: An association with an inhibition of β-catenin signaling

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is a genetic disease that exclusively progresses to renal failure. An important target for the treatment of ADPKD is to reduce cystic cell proliferation. PPARγ agonists such as TZDs are insulin sensitizing agents that have also been reported to decrease tumor growth. Here we tested DH9, a newly synthesized PPARγ agonist on the proliferation of an ADPKD cell line, WT9-12. DH9 showed a potent anti-proliferative activity against ADPKD cells. At high concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In fact, GSK-3b is signicantly involved in key pathological events, namely Tau hyperphosphorylation, amyloidogenesis, inammatory response and ACh decit. 55 As the modulation of GSK-3b activity was also mediated by a diversity of polyphenolic systems [56][57][58] it was decided to screen HCAs and derivatives (compounds 1, 2 and 7-14) towards GSK-3b, at a xed concentration of 10 mM, using a previously described luminescent technique. Recent studies report the ability of compound 1 and its natural phenethyl ester derivative (CAPE) to modulate the Akt/GSK-3b signalling pathway and GSK-3b activity.…”
Section: Gsk-3b Inhibitory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, GSK-3b is signicantly involved in key pathological events, namely Tau hyperphosphorylation, amyloidogenesis, inammatory response and ACh decit. 55 As the modulation of GSK-3b activity was also mediated by a diversity of polyphenolic systems [56][57][58] it was decided to screen HCAs and derivatives (compounds 1, 2 and 7-14) towards GSK-3b, at a xed concentration of 10 mM, using a previously described luminescent technique. Recent studies report the ability of compound 1 and its natural phenethyl ester derivative (CAPE) to modulate the Akt/GSK-3b signalling pathway and GSK-3b activity.…”
Section: Gsk-3b Inhibitory Activitymentioning
confidence: 99%
“…53,54 Moreover, a synthetic hydrocinnamic derivative (DH9) has also been reported to modulate GSK-3b activity by inducing its phosphorylation. 55 As the modulation of GSK-3b activity was also mediated by a diversity of polyphenolic systems [56][57][58] it was decided to screen HCAs and derivatives (compounds 1, 2 and 7-14) towards GSK-3b, at a xed concentration of 10 mM, using a previously described luminescent technique. 59 From the data one can concluded that none of the tested compound displayed noteworthy activity at the established concentration (Table 1).…”
Section: Gsk-3b Inhibitory Activitymentioning
confidence: 99%
“…The TZDs, rosiglitazone and pioglitazone, are currently in clinical use for the treatment of type-II diabetes, while troglitazone was withdrawn from clinical use because it was linked to idiosyncratic liver toxicity [24] . Other non-TZD synthetic ligands include certain non-steroidal anti-inflammatory drugs such as isoxzolidinedione JTT-501 [25] , tyrosine-based GW7845 [26] and DH9, a newly synthesized PPARγ agonist [27] . Naturally occurring compounds that activate PPARγ include long chain polyunsaturated fatty acids which are found in fish oil (e.g.…”
Section: Function Of Pparγmentioning
confidence: 99%
“…13 PPAR-γ activation can also inhibit osteoblastic activity by modulating β-catenin pathway. 14 Prevention of inflammatory state prevents the destructive process and improves periodontal health. 4,7 In this regard, unsaturated carboxylic acids have been shown to exhibit significant inhibitory effects on the pro-inflammatory pathways such as NF-κB and MAPK.…”
Section: Introductionmentioning
confidence: 99%